Defect‐Rich Heterostructured Bi‐Based Catalysts for Efficient CO2 Reduction Reaction to Formate in Wide Operable Windows. Issue 10 (29th July 2022) - Ren, Jiazheng; Long, Xia; Wang, Xiaoting; Lin, Zedong; Cai, Rongming; Ju, Min; Qiu, Yongfu; Yang, Shihe
Abstract : Electrocatalytic reduction of CO2 to formate is believed to be one of the most promising technologies for producing clean fuels and valuable chemicals and for tackling the global warming problem. Herein, a novel synthesis strategy is presented for Bi‐based catalyst in CO2 reduction reaction (CO2 RR). With the addition of acetic acid into the mother solution, heterostructured Bi/Bi2 O3 nanoplates with abundant O vacancies (Bi/Bi2 O3 –Ov ) and tailored coordination environments of the Bi ions are successfully synthesized, which exhibit excellent catalytic activity for CO2 RR and high selectivity for formate generation with wide operable windows of pH (neutral to alkaline) and potential. In particular, the faradic efficiency (HCOOH) reaches ≥90% in a wide potential range of −0.7–−1.35 V versus reversible hydrogen electrode in neutral media, which dwarf most of the state‐of‐the‐art Bi‐based catalysts for CO2 RR reported to date. Combined experimental and theoretical results show that the abundant O vacancies create frustrated Lewis pairs at the heterointerfaces with favorable adsorption characteristics, thereby facilitating the CO2 RR process. This work opens up a new approach to promoting the catalytic activity and selectivity of Bi‐based materials for CO2 RR by combining coordination and heterointerface engineering. Abstract : Defective Bi/Bi2 O3 nanoplates with abundant O vacancies were successfully synthesized by adding acetic acid into the precursor, which exhibit excellent activity for electrocatalytic CO2 reduction and high selectivity for formate generation with wide operable windows. Combined experimental and theoretical results show that the abundant O vacancies created frustrated Lewis pairs thereby facilitating the reduction process.